HUBUNGAN INFEKSI BACTERIAL VAGINOSIS DENGAN KEJADIAN KETUBAN PECAH DINI DI RUMAH SAKIT AL-FATAH AMBON - Gutandjala, Pearly Noveliani; Riyanti, Novy; Latuconsina, Vina Z (PAMERI, 2024)
Background: Premature rupture of membranes (PROM) is a condition in which the amniotic membrane ruptures before labor occurs. It is one of the causes of increased maternal and neonatal morbidity and mortality. Several factors cause PROM such as maternal age, gravida status, incompetentcervix, fetal abnormality, and infections such as Bacterial Vaginosis (BV) infection. Objective: This study aims to determine the relationship between BV infection and the incidence of PROM at Al-Fatah Ambon Hospital. Methods: This research is an observational analytic type of research with acase control approach and sampling using consecutive sampling technique. Data were analyzed using the Statistical Package for the Social Science(SPSS) application. Results: The results of this study showed that out of 30 inpartum mothers, there were 18 mothers with positive BV infection (60%) and 12 mothers with negative BV infection (40%). In the group of mothers with positive BV infection, 12 people experienced PROM and 6 people did not experience PROM. In the group of mothers with negative BV infection, 3 people experienced PROM and 9 people did not experience PROM. Theresults of bivariate analysis with the chi-square test obtained p value = 0.025 and the results of the Odds Ratio analysis obtained an OR = 6.Conclusion: This study showed a significant association between BV infection and the incidence of PROM at Al- Fatah Ambon Hospital.